The effect of bio products Bloom & Grow and Immune system on spring durum and bread wheat productivity in the Chuvash republic - A. G. Lozhkin; О. А. Vasiliev; V. L. Dmitriev; А. V. Kramarenko (Зерновое хозяйство России)
The current paper has presented experimental data on the growth, development, productivity and grain quality of spring durum and bread wheat after use of bio products Bloom & Grow and Immune System on light-gray forest soils of the north of the Chuvash Republic. The trials on the durum wheat cultivation in the conditions of the Chuvash Republic were carried out for the first time. The results of two-year study have showed that the plants treated with bio products had a 7–8 days’ shorter vegetation period. At the same time, the height of the treated bread wheat plants significantly has exceeded the control variant on 12.5 cm; the main head was on 0.4 cm longer, the number of grains in it was 6.1 pieces more, and the grain weight was larger on 0.23 grams. The height of the spring durum wheat plants treated with micronutrients has exceeded the control variant on 25.1 cm, and the length of the main head, the number of grains in it and the grain weight have significantly exceeded the indices of the control variant. 1000-grain weight has exceeded the value of the control variant on 7.28 grams. It has been established that the productivity increase of spring bread wheat was 0.89 t/ha (26.3%) and that of durum wheat was 0.93 t/ha (28.6%) compared with the control variant. The use of bio products Bloom & Grow and Immune System has resulted in an increase of gluten content in spring bread and durum wheat, and in an improvement of the gluten deformation rate to group 1 with the accumulation of minerals. The current study conducted in the vegetation period of 2018–2019 has showed that the bio products Bloom & Grow and Immune System are effective, and combine the properties of a growth stimulator and an immune modulator.